2006
DOI: 10.1590/s0103-84782006000200027
|View full text |Cite
|
Sign up to set email alerts
|

Parametria da associação do midazolam ou diazepam em cães pré-tratados pela atropina e tratados pela dexmedetomidina e quetamina

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
1
1
0
4
Order By: Relevance
“…A shorter anesthetic recovery period occurred in G2 (48 min) as compared to G1 (52 min) and, also with a superior quality. o C what has also been reported for different dissociative anesthesia protocols through continuous infusion 2,3,4 .A greater reduction in body temperature as observed by some authors 5,6,7 is due to the peripheral vasoconstriction and blood central redistribution due to the action of a-2 agonists. This is a controversial effect for a-2 agonists lead to peripheral vasodilatation and heat production reduction.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…A shorter anesthetic recovery period occurred in G2 (48 min) as compared to G1 (52 min) and, also with a superior quality. o C what has also been reported for different dissociative anesthesia protocols through continuous infusion 2,3,4 .A greater reduction in body temperature as observed by some authors 5,6,7 is due to the peripheral vasoconstriction and blood central redistribution due to the action of a-2 agonists. This is a controversial effect for a-2 agonists lead to peripheral vasodilatation and heat production reduction.…”
Section: Resultssupporting
confidence: 58%
“…In dogs treated with medetomidine/isoflurane or isoflurane only , there was an accentuated decrease in BIS as compared to dogs treated with isoflurane only, and so, in conformity with the same authors 56,57,59 . In both groups the electromyography was more accentuated from M2 to M4 characterizing the synergism among the a-2 agonist, buprenorphine and midazolam which suppressed the cataleptoid effects of ketamine and the presence of muscular tonus due to ketamine, the same observed by an author 4 , but not observed by others .. 11,46,60 The reported recovery period is variable 10 , around 76 or down to 64 minutes, approximately. The values were lower than those obtained by other authors and showed that the continuous infusion has an advantage for no significant alterations occurred in the physiological parameter, a better quality and decrease the drugs mass dosis to be utilized.…”
Section: Resultsmentioning
confidence: 61%
“…Valores de BIS entre 70 e 90 indicam sedação de leve a moderada em cães submetidos à anestesia com dexmedetomidina-quetamina, sendo induzidos com midazolam-dexmedetomidina ou diazepam-dexmedetomidina (Hatschbach et al, 2006). Durante um procedimento cirúrgico, os valores de BIS podem diminuir e chegar próximos a zero, em casos de profundidade anestésica, hipotermia e isquemia cerebral (Billard, 2001;Welsby et al, 2003;Hayashida et al, 2003;Morimoto et al, 2005 Assim, o objetivo deste trabalho foi determinar os efeitos de diferentes frações inspiradas de oxigênio, em cães anestesiados com infusão contínua de propofol e mantidos em ventilação espontânea, no monitoramento da depressão do sistema nervoso central, pelo índice biespectral.…”
Section: Introductionunclassified
“…Em estudos semelhantes, alguns autores também observaram um baixo miorrelaxamento com essa associação em capivaras (Hydrochoerus hydrochaeris) [4]. Porém, em outros estudos, foi observado um bom grau de relaxamento, obtendo-se, mais uma vez, uma interação de sinergismo da quetamina com o midazolam em relação aos efeitos miorrelaxantes de ação central, pois o mesmo se sobrepôs aos efeitos cataleptóides causados pela quetamina [8,13].…”
Section: Discussionunclassified